Spectacle Lenses with Aspherical Lenslets for Myopia - Dwiastri Iris Sarwastuti; Sri Kustantini Hendrastuti (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
To evaluate the effectiveness of spectacle lenses with aspherical lenslets in myopia control. Literature retrieval on PubMed, Cochrane Library, Embase, and Web of Science databases was conducted until December 29, 2023. Studies were selected based on predefined inclusion and exclusion criteria, and RevMan 5.3 software was used for meta-analysis. A total of four randomized controlled trials (RCTs) were included in this meta-analysis, involving 770 myopic children. The results demonstrated that spectacle lenses with aspherical lenslets significantly reduced the progression of myopia in children when compared with single vision spectacle lenses (SVLs) (WMD = -0.21 D, 95% CI: -0.41, -0.01, p < 0.05). However, no significant difference was found in the control of axial length (AL) growth in myopic children (WMD = -0.10 mm, 95% CI: -0.21, 0.01, p = 0.07). The results indicated that spectacle lenses with aspherical lenslets were more effective in controlling the progression of myopia (OR = 0.73, 95% CI: 0.52, 1.20, p < 0.001) and delaying the growth of AL (OR = 44.25, 95% CI: 8.84, 221.58, p < 0.001) compared to SVLs. Spectacle lenses with aspherical lenslets can effectively control the progression of myopia compared with SVLs, but they do not significantly delay the growth of AL.